Tumor Necrosis Factor-Alpha and Interleukin 6 localization in the Umbilical Cord Tissue of Pregnant Women with Preeclampsia: Smokers and Non-smokers - Yediel-Aras, Sukran; Goktug-Kadioglu, Berrin; Gezer, Arzu; Bakir, Buket; Karadag-Sari, Ebru (Puerto Rico Health Sciences Journal, 2024)
Objective: In this study, the localization of tumor necrosis factor alpha (TNF-α) and interleukin (IL) -6 in the umbilical cord tissue of pregnant women with preeclampsia who smoke and in those who do not smoke was investigated using immunohistochemical methods. Methods: The sample groups consisted of a control group, cigarette smokers, preeclampsia, and cigarette smokers with preeclampsia. Histological and immunohistochemical methods were applied to the tissue samples. Results: It was determined that there were varying degrees of edemato s change in the layers of arteries and veins in the preeclampsia and the cigarette smokers with preeclampsia groups, with a statistically significant level of difference in thickness compared to the other groups. In addition, different levels of TNF α and IL-6 immunoreactivity were detected in the umbilical cord tissue across all the groups. In the preeclampsia group, TNF-α immunoreactivity was found to increase in the arterial muscle layer. Moreover, IL-6 immunoreactivity was found to decrease in the arterial endothelium and muscle layers in the cigarette smokers, preeclampsia, and cigarette smokers with preeclampsia groups and increase in the venous endothelium and muscle layers. In addition, immunoreactivity increased in the amniotic epithelium in the cigarette smokers with preeclampsia group. Discussion: In conclusion, the differences in cytokine levels between the cigarette smokers, preeclampsia, and cigarette smokers with preeclampsia groups were thought to be caused by responses of the maternal immune system and histopathological changes in the umbilical cord tissue.